1996
DOI: 10.1016/s0092-8674(00)81255-6
|View full text |Cite
|
Sign up to set email alerts
|

E2F-1 Functions in Mice to Promote Apoptosis and Suppress Proliferation

Abstract: Members of the E2F transcription factor family (E2F-1-E2F-5) are believed to be critical positive regulators of cell cycle progression in eukaryotes although the in vivo functions of the individual E2Fs have not been elucidated. Mice were generated that lack E2F-1 and, surprisingly, these mice develop and reproduce normally. However, E2F-1-/- mice exhibit a defect in T lymphocyte development leading to an excess of mature T cells due to a maturation stage-specific defect in thymocyte apoptosis. As E2F-1-/- mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
553
5
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 715 publications
(596 citation statements)
references
References 61 publications
30
553
5
7
Order By: Relevance
“…We assessed the contribution of the genetic background to the phenotype by breeding the animals to C57Bl/6J‐strain, which showed that genetic background had a strong influence on the severity and the time course of the phenotype associated with E2F1 loss. In the previous studies on the E2F1 −/− mice the testicular atrophy has been reported from the age of 3 months onwards (Field et al ., 1996; Yamasaki et al ., 1996; Hoja et al ., 2004). In contrast, in C57Bl/6 genetic background significant testicular atrophy occurred already at P20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed the contribution of the genetic background to the phenotype by breeding the animals to C57Bl/6J‐strain, which showed that genetic background had a strong influence on the severity and the time course of the phenotype associated with E2F1 loss. In the previous studies on the E2F1 −/− mice the testicular atrophy has been reported from the age of 3 months onwards (Field et al ., 1996; Yamasaki et al ., 1996; Hoja et al ., 2004). In contrast, in C57Bl/6 genetic background significant testicular atrophy occurred already at P20.…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were carried out according to the institutional and ethical policies of the University of Turku and approved by the local ethics committee on animal experimentation. The E2f‐1 −/− mice B6;129S4‐E2f1tm1Meg/J (Field et al ., 1996; Yamasaki et al ., 1996) were purchased from the Jackson Laboratory. C57BI/6J control animals were obtained from the breeding stocks of the Central Animal Laboratory of the University of Turku.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many genes involved in apoptosis are direct targets of E2F, overexpression of E2F 1 has been shown to induce apoptosis, and E2F 1À/À thymocytes are defective in undergoing apoptosis (Field et al, 1996). Whether this ability to induce apoptosis is restricted to E2F 1 or is shared by other activating E2Fs is still unclear.…”
Section: Cell Cycle Roles Of the Rb Family Of Proteinsmentioning
confidence: 99%
“…Recent evidence suggests that it is likely that di erent members of the E2F family may perform distinct functions in an organism. First, mice nullizygous for the E2F-1 gene display a strong predisposition to hyperplastic growth and tumor formation (Field et al, 1996;Yamasaki et al, 1996). These results suggest that other members of the E2F family cannot compensate for the functional loss of E2F-1.…”
Section: Introductionmentioning
confidence: 99%